2014
DOI: 10.1152/ajpheart.00889.2013
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves cardiac function and remodeling by inhibition of sympathoexcitation in chronic heart failure rats

Abstract: Chronic heart failure (CHF) is responsible for significant morbidity and mortality worldwide, mainly as a result of neurohumoral activation. Acupuncture has been used to treat a wide range of diseases and conditions. In this study, we investigated the effects of electroacupuncture (EA) on the sympathetic nerve activity, heart function, and remodeling in CHF rats after ligation of the left anterior descending coronary artery. CHF rats were randomly selected to EA and control groups for acute and chronic experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
2
27
0
2
Order By: Relevance
“…Our study shows a reduction in LV hypertrophy in the EA group. These data corroborate the findings demonstrating that EA improved the cardiac structure and function in animals with this model of HF and additionally reduced the sympathetic activity (Ma et al, 2014). However, Ma et al (2014) did not evaluate the baroreflex sensitivity and, in this context, our study demonstrated for the first time that EA improves baroreflex function in HF rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study shows a reduction in LV hypertrophy in the EA group. These data corroborate the findings demonstrating that EA improved the cardiac structure and function in animals with this model of HF and additionally reduced the sympathetic activity (Ma et al, 2014). However, Ma et al (2014) did not evaluate the baroreflex sensitivity and, in this context, our study demonstrated for the first time that EA improves baroreflex function in HF rats.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, a well-design study demonstrated that EA attenuates sympathetic over activity, improves cardiac function and remodelling and reduces infarct size in HF rats and postulated EA as a novel and potentially useful therapy for treating HF (Ma et al, 2014). Furthermore, most studies show only short-period acupuncture applications, which makes it difficult to prove the long-lasting effects of acupuncture in chronic situations.…”
Section: Introductionmentioning
confidence: 99%
“…) or electroacupuncture (Ma et al . ) inhibited CSAR and sympathetic activity, and improved cardiovascular dysfunction.…”
Section: Enhanced Csar In Chfmentioning
confidence: 90%
“…Li et al [26] demonstrated that an electroacupuncture stimulation at the median nerve reduced reflex-regional myocardial ischemia in anesthetized cats. Ma et al [27] showed that treating heart failure rats with electroacupuncture for 1 week markedly increased the left ventricular ejection fraction, reversed the enlargement of the left ventricle, and shrunk the infarct size. Lima et al [28] reported improvements in hemodynamic parameters in heart failure rats by chronic electroacupuncture at the ST36 acupoint.…”
Section: Clinical Perspectivesmentioning
confidence: 99%